ICT mediated collaborative work in system dynamics learning (2015)
Although mathematical modeling is a general engineering skill, problem analysis and solution design conventional tools in systems engineering, such as use case diagrams, class diagrams and relational diagrams among others, are often not supported by a mathematical model or this is not made explicit during learning. This may affect the ability of the systems engineer for interdisciplinary work, whose participation in the requirements determination phase of the software development process can be reduced to be notified of the needs identified by the other actors, without a critical contribution of its party. This paper presents results of research that show the favorable effect of collaborative work mediated by information and communication technology ICT on System Dynamics mathematical modeling skills developing by Systems Engineering students.